Architecting CSS the programmer's guide to effective style sheets - Dowden, Martine (Apress, 2020)
Leverage various CSS features in combination with popular architectures in order to bring your style sheets back under your control. While CSS is the primary technology used for building beautiful web user interfaces, the style sheet files themselves are often quite ugly; left chaotic and unstructured through lack of a consistent architectural approach. By addressing the structure of your style sheets in the same way that you do with code, see how it is possible to create style rules that are clean and easy to read. Dig deep into CSS fundamentals and learn how to use the available selectors to build powerful rules. You will learn how to use cascading, inheritance, pseudo-classes, pre-processors, and components to produce cleaner, DRY-er style sheets, and how to let these features work for you instead of leading you down the road of rule duplication and design inconsistencies. Embrace the clean, semantic HTML to make your code easier to read, while supporting accessibility and assistive technologies. Separate the concerns of layout and style to simplify dynamic theming and white labeling, making you a marketing hero. Once you've finished this book you will have an advanced knowledge of CSS structures and architectural patterns that will take the pain out of style sheets for you (and your coworkers), and help you implement designs faster and easier than ever before. You will: Understand the core CSS fundamentals of Inheritance, Cascading, and Specificity Work with architecture and design patterns for better organization and maintenance Maximize code reuse with CSS precompilers Review the strengths and weaknesses of popular architecture patterns.
Includes bibliographical references and index
Keywords: Cascading style sheets; Feuilles de style en cascade; Web programming; Computers; Web; Web Programming